Extreme variability of expression of a Sonic Hedgehog mutation: attention difficulties and holoprosencephaly. Issue 4 (1st April 2002) - Heussler, H S; Suri, M; Young, I D; Muenke, M
Abstract : Holoprosencephaly (HPE) is a clinically variable and genetically heterogeneous central nervous system (CNS) malformation. Alobar HPE, which is its most severe form, is associated with a poor prognosis. At the milder end of the HPE spectrum microcephaly, hypotelorism, and single central maxillary incisor may be recognised. Currently, four genes have been identified for this condition. These include Sonic Hedgehog ( SHH ) on chromosome 7q36, which is thought to be responsible for a significant proportion of autosomal dominant HPE. We report an index case with alobar holoprosencephaly caused by an SHH mutation and six members of his family over two generations with this mutation, with a broad range of clinical presentation, including attention deficit hyperactivity disorder (ADHD). The combination of microcephaly, hypotelorism, subtle midline facial anomalies, and ADHD within a sibship should alert the physician to the possible diagnosis of HPE.